“Culture is a shadow”, language as a shade Fragments of a dead language, Naka’ela - Collins, James T. (UI Scholars Hub, 2021)
One of the distinctive languages of Central Maluku, Naka’ela, was once spoken by a remnant language community on the north coast of Seram. Relying on data collected in Seram in 1978, Naka’ela has been among the Central Maluku languages included in studies of morphophonology (Collins 1983a, 1983b), areal phonology shift (1982, 2018a), and language classification (Collins 1983a). A fallacious, mechanistic classification of Naka’ela (Mahsun et al. 2008; Mukhamdanah 2015) was also published and has been recently disproven (Collins 2019a, 2019b). This essay will review some of the aspects of the Naka’ela language system by exploring what we can discern about verbal conjugation systems and genitive paradigms in this Central Maluku language. Based on contemporary reports from Seram (Sadrach Latue, p.c., 27-10-2018), the Naka’ela language, like so many others in Central Maluku, is no longer spoken; nor are there “rememberers” of this extinct language. In this setting of dead and forgotten languages, we recall the brutal genocides and culture murders in Australia (Daniel Nettle and Suzanne Romaine 2000). Recently, Dianne Biritjalawuy Gondarra, a Yolngu woman from northern Australia, explained that “culture is a shadow, it’s something that follows your everywhere, and part of culture is language, which connects me back to my land” (James Griffths 2020). This essay is intended to shed more light on Naka’ela and the complex setting of fading multilingualism in Central Maluku. The displaced, disregarded Naka’ela community survives in Seram, their land, but their language is only a shade, a ghostly memory.